Increasing Students' Digital Literacy Through the Use of Google Cardboard Media on the Theme of My Dreams In Class IV of Elementary School - Triandayani, Anis; Fadlozi, Yuslim Ma'ruf; Barzegar, Somayeh; Quijano JR, Gregorio N. (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine and improve students' digital literacy using Google Cardboard media for class IV students at Elementary School and assessing the extent to which students' participation and involvement in learning activities using Google Cardboard can motivate them to actively learn. Methodology: This research is classroom action research. The subjects of this research were 25 grade IV students at Elementary School. The object of the research is to increase students' digital literacy through Google Cardboard media. Data techniques use tests and observations. The research instrument uses observation sheets and test questions or evaluation of learning outcomes. Main Findings: The results of the study showed that before the implementation of Google Cardboard media on the theme of my dreams, 5 students (20%) had completed it and 20 students (80%) had not completed it and the class average score was 60%. However, after learning using Google Cardboard media in learning the theme of my dreams in cycles 1 and II, data was obtained that student learning outcomes increased. With the increase that occurred in students who had reached 88%. Novelty/Originality of this study: The novelty of this research is that through the use of Google Cardboard with a focus on the theme